Guillermo Verdecchia y la frontera en la literatura contemporánea canadiense de la diáspora - Maver, Igor; Zorc-Maver, Darja (Acta Literaria, 2011)
Contemporary diasporic literary authors in Canada are today mostly seen as transcultural authors in the global cross-border English-speaking cultural collage space and in the Canadian multiethnic society. The socalled minority literature has in effect become part of the mainstream and no longer merely a veneer of the much coveted and publicly proclaimed, albeit not always practically effectual multiculturalism. Canadian diasporic writing thus has to be considered anew within the context of a new interAmerican transborder integration, which has substantially changed the field of identity politics, the very concept of ethnicity and the need for its redefinition, as well as the various cultural/literary practices of a collective and individual dynamic identity construction.